Pengaruh Promosi Online dan Harga Terhadap Keputusan Pembelian Jasa Produksi Pakaian Jadi di PT Menjahit Mimpi Indonesia (DIJAIT) - Sadiyah, Titin; Assaf, Rizka Aula (Jurnal Manajemen dan Bisnis Kreatif, 2024)
The economy in Indonesia in the third quarter of 2023 experienced growth of 4.94% amidthe global economic slowdown compared to the third quarter of 2022. The small micro andmedium enterprise sector or known as MSMEs also has an important influence oneconomic development in Indonesia. PT Menjahit Mimpi Indonenesia is one of theMSMEs engaged in apparel production services in collaboration with convection businessactors and located in Cimahi City. This study aims to see the effect of online promotionand price on purchasing decisions at PT Menjahit Mimpi Indonesia partially andsimultaneously. A quantitative approach with verification research design is the methodused in this study. The population taken in this study were consumers of PT MenjahitMimpi Indonesia who made at least one transaction totaling 132 people. The Slovinformula was used in calculating a sample of 57 consumers. This study shows the resultsthat online promotion and price have a positive and significant effect on purchasingdecisions at PT Menjahit Mimpi Indonesia partially and simultaneously.